The Role of Universities in Guarding Moderation and Nationality: The Role of The UPN “Veteran” Jawa Timur Academic Community in Caring for Religious Moderation and Nationalism - Rohmatul Faizah; Ahmad Baedowi; Cholid Fadil (Nusantara Science and Technology Proceedings, 2021)
Islam recommends that its followers take the middle path, not extreme left or right (tawasuth or moderate). The nature of tawasuth is part of religious moderation that must be instilled in students so that in life they can have a moderate attitude toward the life of the nation and state. Religious moderation is necessary and taught to students to become conciliatory, compassionate, and tolerant human beings in the future. The involvement of the higher education academic community in providing an understanding of the nature of tawasuth for students needs to be developed and echoed. The academic community of higher education needs to guard the understanding of moderation and rationality, mutual affection, mutual love, mutual respect, and mutual assistance in goodness. Because with this understanding, students can implement it in everyday life. This research described the role of universities in guarding religious and national moderation. The Indonesian nation has cultural assets and spiritual assets which are basic social capital (especially in a multicultural society). Institutions such as universities must be able to establish cooperative relationships with the community to realize the expected social transformation. Universities have a strategic role in guarding religious moderation by developing moderate attitudes and culture in students to behave tolerantly, critically, respectfully, and inclusively. This research used the library research method with a descriptive analysis approach.